Pengaruh Daya Tarik Wisata dan Fasilitas Terhadap Minat Berkunjung Kembali Dengan Kepuasan Sebagai Variabel Intervening - Achmad Zain Ibrahim; Dewi Noor Susanti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of tourist attractions and facilities on the intention to revisit Jembangan Wisata Alam, with visitor satisfaction serving as a mediating variable. The respondents were individuals aged 18 years and above who had visited Jembangan Wisata Alam within the past 30 days. Data were collected using a questionnaire, and the sampling technique employed was non-probability sampling through purposive sampling. Data analysis included validity and reliability tests, classical assumption testing, hypothesis testing, correlation analysis, path analysis, and Sobel test. Data processing was conducted using SPSS version 22 for Windows. The results showed that (1) tourist attractions have a positive and significant effect on visitor satisfaction; (2) facilities have a positive and significant effect on visitor satisfaction; (3) tourist attractions have a positive and significant effect on revisit intention; (4) facilities have a positive and significant effect on revisit intention; (5) tourist attractions have a positive and significant effect on revisit intention through visitor satisfaction; (6) facilities have a positive and significant effect on revisit intention through visitor satisfaction; and (7) visitor satisfaction has a positive and significant effect on revisit intention. These findings emphasize the importance of improving tourist attractions and facilities as key strategies to enhance visitor satisfaction and loyalty toward tourism destinations.